Responsive front land boundary design parameters on urban main road corridors (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study critically evaluates the design of front land boundaries for buildings situated along Sudirman Street, Jakarta. The assessment of design quality was conducted through systematically observed parameters, including access configuration, boundary height, transparency, materiality, signage, and lighting, each grounded in established urban design principles and the prevailing regulatory framework. Data were collected via systematic field observations of 24 buildings located along the west side of Sudirman Street. The results reveal considerable variation in design responsiveness: only six buildings exhibit high responsiveness, characterized by permeable interfaces, as well as thoughtfully integrated lighting and signage, whereas the majority demonstrate moderate to low responsiveness due to limited transparency and insufficient visual connectivity with the public realm. These findings are interpreted within the frameworks of urban design theory, CPTED (Crime Prevention Through Environmental Design), and Jakarta’s regulatory standards governing land boundaries, highlighting that design elements such as transparency and lighting play a critical role in mediating the interaction between buildings and street life. This study thereby contributes to an empirical understanding of how the qualitative attributes of front land boundary design enhance urban spatial experience and responsiveness within densely developed metropolitan corridors.
Keywords: Design; Front boundary; Responsivenes; Sudirman street